Faktoring jako sposób poprawy płynności finansowej przedsiębiorstwa - Filip, Paulina (Faktoring as a Special Form of Financing in Enterprises, 2009)
Factoring is a financial instrument that combines working capital financing, credit risk protection, accounts receivable bookkeeping and collection services. It is offered under an agreement signed between the factor and a seller. A company financing their current activity with factoring receives the financing immediately upon the sale of goods so it can well manage their finances as well as reduce the risk of deficiencies in payment and reduce the financial risk. Factoring is especially recommended for the enterprises that sell goods and services with a deferred payment The factoring industry in Poland has already noted a record growth in the last years. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 107-113